Antibacterial, Antifreezing, Stretchable, and Self‐Healing Organohydrogel Electrode Based Triboelectric Nanogenerator for Self‐Powered Biomechanical Sensing. Issue 15 (3rd April 2022) - Zhang, Jiaming; Zhao, Xinyang; Wang, Zhuo; Liu, Zhirong; Yao, Shuncheng; Li, Linlin
Abstract: Flexible and wearable electronic devices have broad applications in human–machine interaction and personal health monitoring. To meet different application scenarios, in this work, an antibacterial, antifreezing, stretchable, and self‐healing organohydrogel‐based triboelectric nanogenerator (O‐TENG) for biomechanical energy harvesting and self‐powered sensing is developed. Through integrating Ag nanoparticles on reduced graphene oxide sheets (Ag@rGO) into poly(vinyl alcohol)‐polyacrylamide (PVA‐PAAm) dual‐network organohydrogel with dynamic borate bonds, denoted as Ag@rGO/PVA‐PAAm, the organohydrogel has high conductivity, good stretchability, and antifreezing and self‐healing properties. When using Ag@rGO/PVA‐PAAm as the electrode layer of O‐TENG, it can effectively inhibit Gram‐negative bacterium E. coli and Gram‐positive bacterium S. aureus while showing high cytocompatibility. With the self‐healing and antifreezing property, the fabricated O‐TENG has stable output performance under room temperature and low temperature of −30 °C, even after Ag@rGO/PVA‐PAAm is damaged and self‐healed. This O‐TENG is demonstrated to harvest mechanical energy and is used as self‐powered sensors for recognizing handwriting and wrist motion state. This work provides a new pathway for design and application of multifunctional flexible wearable devices. Abstract : The self‐powered and wearable bioelectronics with antibacterial, stretchable, low‐temperature resistance, and self‐healing properties are highly pursued, which are seldom realized simultaneously. In this work, a multipurpose self‐powered triboelectric sensor with all these properties, based on a multifunctional antibacterial, stretchable, antifreezing, self‐healing organohydrogel electrode, is fabricated. The triboelectric sensor is used for self‐powered handwriting recognition and biomechanical sensing, even under extreme low temperatures.